Biomechanical analysis of scissor lunge and drop jerk in clean and jerk - Pan, H. J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Scissor lunge and drop jerk are two coexisting techniques in clean and jerk. Scissor lunge is the most conventional technique. Since Chen Jin-kai, who is a Chinese weightlifter, broke nine world records continually by the drop jerk technique, many weightlifters have used this technique. Zhan Xu-gang, another Chinese weight lifter achieved great success by the jerk technique in the Olympic Games. A very few studies compared the essential elements of these techniques and the advantages and disadvantages between scissor-lunge and drop jerk. However, there are different conclusions between the studies. This paper contains a comprehensive analysis of the link kinematics of two techniques and the mechanical characteristic of muscles and provides information that coaches and weightlifters can use to choose an appropriate techniques accurately. Methods Eight elite Chinese weightlifters were selected. The two techniques of scissor-lunge and drop jerk in clean and jerk were recorded using a JVC9600 digital video camera and analysed with a SIMI-Motion video system. The bar height of the chest rest before the pull, the bar height when the brake was finished and the supporting and bar height when the movement was finished were measured. The knee angle at the above instances were also measured and analysed by a muscular-mechanical model of the movement of the legs. Results The bar height of chest rest before the pull is 1.54±0.13 m and at the end of the movement the bar height is 1.92±0.97m. In the scissor lunge technique at the end of the brake and supporting the bar height is 1.75±0.87m. This height is more (0.21±0.05 m) than the chest rest before the pull. In the drop jerk technique, at the end of the brake and supporting the bar height is 1.41±0.89 m. This height is lower (-0.21±0.05m) than the chest rest before the pull. During the scissor-lunge and drop jerk techniques respectively, the knee angle is 124.2°±5.8° and 125.3°±4.2°at the beginning of the brake and 118 °±9.4° and 58.5°±6.3° at the end of the brake and 164.1°±4.2° and 160.2°±3.5° when the pulling is finished. In the scissor lunge and drop jerk techniques respectively the change in the knee angle is 6.2°±2.1° and 66.8°±5.5° in the course of the brake and 46.1°±4.7°and 101.7°±8.3° in the process of pulling.